Natural caspase inhibitors - Salvesen, Guy (Henry Stewart Talks, 2007)
Apoptosis, Proteolytic mechanisms, Caspases, Activation mechanisms, Natural caspase inhibitors, Viral inhibitors, IAPs, Inhibitory mechanisms, IAP antagonists, Theory of activating apoptosis by de-repression of caspase inhibition